Foliar sources of boron and manganese in soybean and zinc plants in corn plants complexed with polyols in nutritional status and in production - Neto, André Mendes Coutinho [UNESP]; da Silva, Gilmara Pereira; Coutinho, Edson Luiz Mendes [UNESP]; Prado, Renato de Mello [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2020)
Alternative sources of micronutrients have appeared on the market from B, Mn, and Zn complexes with polyols without scientific evidence on their agronomic effects compared to conventional sources, which is a concern when high fertilizer efficiency is sought Leaf. This study’s objective was to evaluate the levels of Mn, B, and Zn leaf and grain and grain yield as a function of foliar application of doses and sources of Mn and B in soybean and Zn maize. They studied different sources of Mn (manganese sulphate, Mn-EDTA chelate, and Mn complex with lignosulfonate and with polyol), B (boric acid, B complex with polyol) in soybean and Zn (zinc sulfate, Zn-EDTA and Zn complex with polyol). Foliar application of sources and doses of Mn and B in the soybean and Zn crops in the maize crop does not influence plant nutrition and grain production. Foliar application of soluble sources, chelates, and alternative sources of Mn, B in the soybean, and Zn crops in maize crops present similar agronomic efficiencies in plant nutrition and grain production.
Fuentes foliares de boro y manganeso en plantas de soya y fuentes de zinc en plantas de maíz suplementadas con polioles en estado nutricional y en producción del cultivo
Keywords: Glycine max; Micronutrients and foliar fertilization; Zea mays